2006
DOI: 10.1097/00005131-200607000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Injury From Thoracic Pedicle Screw Placement in a Polytrauma Patient

Abstract: The authors present a case report illustrating a visceral complication that may occur as result of thoracic pedicle screw placement. The case describes the previously unreported occurrence of esophageal impingement secondary to anterior vertebral body perforation by a pedicle screw at the third thoracic vertebra. This case highlights the challenge of thoracic pedicle screw placement and the importance of preoperatively measuring the maximum anterior-posterior dimension of the vertebral body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…36,[39][40][41][42][43][44][45][46] Despite none of the perforations caused screw-related complications in this study, there were a grade 2 medial perforation which may result in neurologic complications and a grade 2 as well as a grade 3 ( Figure 3) anterior perforation which may risk injury to mediastinal visceral structures. O'Brien et al 47 had reported a case of oesophageal injury after instrumentation of the T3 vertebrae due to backward pressure from the endotracheal tube and trachea that pushed the oesophagus unto the tip of the anterior perforated screws. Belmont et al 39 had reported a higher incidence of anterior perforation from T1 to T4 vertebra compared to T5 to T12 with open pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…36,[39][40][41][42][43][44][45][46] Despite none of the perforations caused screw-related complications in this study, there were a grade 2 medial perforation which may result in neurologic complications and a grade 2 as well as a grade 3 ( Figure 3) anterior perforation which may risk injury to mediastinal visceral structures. O'Brien et al 47 had reported a case of oesophageal injury after instrumentation of the T3 vertebrae due to backward pressure from the endotracheal tube and trachea that pushed the oesophagus unto the tip of the anterior perforated screws. Belmont et al 39 had reported a higher incidence of anterior perforation from T1 to T4 vertebra compared to T5 to T12 with open pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…15 -20 However, the esophagus also seems at risk of injury with anterior penetrated pedicle screw in the PT region. O'Brien et al 11 reported a case of esophageal injury secondary to anterior vertebral body perforation by TPS at T3 level. In our clinical practice, we also found that anterior wall penetration of the vertebral body poses high risk of injury to the esophagus in the PT curve.…”
Section: Discussionmentioning
confidence: 99%
“…O'Brien et al 11 reported a case of anterior cortical perforation by a pedicle screw at the T3 level causing esophageal injury. In our clinical practice, we also noticed that the esophagus is at a high risk of injury in cases of anterior cortical penetration in the PT region of AIS patients ( Figure 1 ).…”
mentioning
confidence: 99%
“…47 Although minor misplacement poses little risk of injury, a displacement greater than 4 mm is associated with a high risk of injury to vital structures depending on the instrumented level. 45 Nerve Root or Spinal Cord Injury. The overall incidence of nerve root or spinal cord injury is rare, ranging between 0.6% and 11%.…”
Section: Management Of Screw-related Complicationsmentioning
confidence: 99%
“…A too long pedicle screw in thoracic region may potentially injure the esopha- gus, the pleura, and the lung. O'Brien et al 45 reported a case of esophagus impingement from pedicle screws at T-3. Esophagoscopy showed a discrete area of attenuation of the mucosa but no perforation.…”
Section: Management Of Screw-related Complicationsmentioning
confidence: 99%